Non-stick layer, manufacturing method thereof and non-stick cooker
By applying a non-stick layer of gap structure formed by stacking microscale materials on the cookware, the problem of the existing non-stick cookware being prone to aging or decomposition at high temperatures is solved, and the good initial and long-lasting non-stickness of the cookware is achieved.
Patent Information
- Application Number
- CN202411668506.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
Existing non-stick cooking utensils are difficult to have both initial non-stick and long-lasting non-stick, and are prone to aging or decomposition at high temperatures.
A non-stick layer of gap structure formed by a stack of microscale materials is adopted. The gap structure has multiple micro-scale gaps and nano-scale gaps, which can allow water molecules and air to pass through and prevent oil molecules from passing through, thus forming an air float effect. .
The cookware has achieved a good air floatation effect during heating, reducing direct contact between food and the surface of the cookware, improving initial and long-lasting non-stickness, and maintaining stability in high temperature environments.
Smart Images

Figure CN119453768A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of non-stick cookware, and more specifically, to a non-stick layer for cookware and a manufacturing method thereof, and non-stick cookware. Background Art
[0002] In the art, fluorine coating is a liquid non-stick coating. Although the non-stick layer made of fluorine coating has excellent initial non-stick properties, it is easily damaged by a spatula and is easily aged or decomposed due to high temperature during use. This will seriously affect the service life of the coating formed by fluorine coating, resulting in the formation of a coating with poor long-term non-stick properties.
[0003] Therefore, developing a non-stick layer for pots and pans having both initial non-stick properties and lasting non-stick properties remains a problem that needs to be solved. Summary of the invention
[0004] Therefore, the object of the present application is to provide a non-stick layer for cookware and a method for manufacturing the same, and non-stick cookware, so as to solve the problem that the existing non-stick cookware cannot have both initial non-stick properties and lasting non-stick properties.
[0005] According to a first aspect of the present application, a non-stick layer is provided for use in cookware, wherein at least a surface layer of the non-stick layer has a layer gap structure, the layer gap structure is formed by stacking a plurality of micro-scale flaky materials, the micro-scale flaky materials are formed by stacking a plurality of nano-scale flakes, the layer gap structure has a plurality of micron-scale gaps, and a plurality of nano-scale gaps are provided between adjacent micron-scale gaps.
[0006] According to the non-stick layer provided by the embodiment of the present application, a plurality of micro-scale-like materials can form a criss-cross interlayer structure (similar to the stack formed by the arrangement of fish scales) by stacking, and the interlayer structure formed not only has a large surface area, but also can provide a gap that is only conducive to the passage of water molecules and / or air. In this way, during the heating process of the cooker, the surface layer of the interlayer structure can capture and retain air and water vapor, and these gases expand when heated between the interlayers to form a good flotation effect between the interlayers, thereby reducing the direct contact between the food and the surface of the cooker and reducing the possibility of sticking to the pan. At the same time, the gaps in the surface layer of the interlayer structure do not allow oil molecules to pass through, that is, oil molecules can be prevented from passing through, so that the stability of the flotation effect formed between the interlayers can be ensured. This is because, on the one hand, if the oil molecules can pass through these interlayers, then they will occupy the space originally belonging to air and water vapor, thereby affecting the flotation effect, or inhibiting its formation. On the other hand, if the oil molecules can pass through these interlayers, then the oil molecules may adhere to the inner wall of the interlayer, causing the interlayer structure to become blocked, thereby further destroying the flotation effect and affecting the non-stickiness of the cooker. Thus, the cookware according to the present application has good initial non-stick properties and long-lasting non-stick properties.
[0007] In some embodiments, the size of the micron-scale gap is 1 micron-10 microns, and the size of the nanoscale gap is 50 nanometers-200 nanometers.
[0008] In these embodiments, the non-stick layer having a layer gap structure with both micrometer-scale gaps and nanometer-scale gaps of the above sizes has a higher uniformity of the layer gap structure and a more significant air flotation effect, and can have improved initial non-stickiness and lasting non-stickiness.
[0009] In some embodiments, the nano-scale gaps and the micro-scale gaps are irregularly shaped.
[0010] In these embodiments, the irregular shape can provide more surface variations and spatial distribution, which helps the gas (such as air and water vapor) to be more evenly distributed and expanded in the gap, thereby enhancing the stability and uniformity of the air floating effect.
[0011] In some embodiments, the micro-scale flake material is a micron-scale flake, and the surface area of the micron-scale flake is 50 square microns-3600 square microns, and the thickness is 1 micron to 5 microns.
[0012] In these embodiments, micron-sized flakes having a specific surface area and thickness can be effectively micro-melted and deposited to form a non-stick layer under the action of a subsequent energy source, thereby facilitating the realization of optimal performance of the non-stick layer.
[0013] In some embodiments, the surface area of the nanoscale flakes is 4900 square nanometers to 360,000 square nanometers, and the thickness is 10 nanometers to 50 nanometers. In this way, they can be combined to form micron-scale flakes with predetermined gaps, so that the non-stick layer formed by the micron-scale flakes has a desired layer gap structure, thereby paving the structure for forming an air flotation effect to enhance the non-stickiness of the non-stick layer.
[0014] In some embodiments, in the micro-scale flaky material, the gap between adjacent nano-scale flaky materials is in the range of 50 nanometers to 200 nanometers. The micro-scale flaky materials formed by the nano-scale flaky materials with such gaps are used as micro-scale flaky materials. Since the gaps inside the micro-scale flaky materials are largely retained during the process of forming the non-stick layer, the nano-scale gaps in the formed interlayer structure can be ensured, so that the desired interlayer structure can be obtained to obtain the desired non-stick layer.
[0015] In some embodiments, the micro-scale flaky material is an inorganic non-metallic material having a certain hardness and high temperature resistance, so that the formed non-stick layer can remain stable under high temperature and wear environments.
[0016] In some embodiments, the inorganic non-metallic material includes micaceous iron oxide or a modified product of micaceous iron oxide. The above materials have low surface energy and high wear resistance, which can ensure that the non-stick layer formed by them has certain non-stick properties.
[0017] In some embodiments, the non-stick layer includes a plurality of stacked sub-layers, and the interlayer structures of the sub-layers are arranged in a staggered manner in the thickness direction of the non-stick layer. There are gaps between adjacent micro-scale materials in each sub-layer. On the one hand, the gaps in the surface layer of the non-stick layer can allow water molecules and / or air to pass through and prevent oil molecules from passing through. It is similar to the stacking method of fish scales, and has a gap size and gap distribution that is convenient for forming an air flotation effect. On the other hand, the probability of forming through holes in the thickness direction of the non-stick layer as a whole is small, which can improve the corrosion resistance of the non-stick layer to a certain extent.
[0018] In some embodiments, the thickness of the non-stick layer is 10 microns to 150 microns, so that the properties of the cookware in terms of weight, non-stickiness, and thermal conductivity can be balanced, so that the overall performance of the cookware is better. And / or, the hardness of the non-stick layer is 600HV to 1100HV, so that the non-stick layer of such hardness can balance wear resistance and flexibility, and has sufficient wear resistance to resist scratches and wear, and can maintain good flexibility to avoid cracks or peeling under temperature changes or mechanical stress. And / or, the temperature resistance of the non-stick layer is 800℃-1200℃, so that the cookware with the non-stick layer can be not afraid of high temperatures and has longer durability.
[0019] In some embodiments, a fatty acid salt modified layer is connected to the surface of the non-stick layer, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the non-stick layer.
[0020] In these embodiments, a fatty acid salt modified layer is further connected to the non-stick layer. The fatty acid salt modified layer is compatible with oils and fats. Therefore, by utilizing the oil film non-stick principle, the initial non-stick property and the lasting non-stick performance of the cookware are improved to a certain extent.
[0021] In some embodiments, the oil comprises at least one of glyceryl stearate, glyceryl palmitate and glyceryl oleate.
[0022] In these embodiments, the oils and fats can be connected to the surface of the non-stick layer and can have low surface energy after forming corresponding salts, thereby further improving the initial non-stick property and the long-lasting non-stick performance of the cookware.
[0023] According to a second aspect of the present application, a method for manufacturing a non-stick layer is provided, wherein the method comprises the following steps:
[0024] Providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes;
[0025] The surface of the micro-scale flaky material is micro-melted, so that the micro-scale flaky material is stacked to form a non-stick layer having a layer structure with a plurality of micron-scale gaps, wherein a plurality of nano-scale gaps are provided between adjacent micron-scale gaps.
[0026] According to the method for manufacturing a non-stick layer provided in an embodiment of the present application, a specific micro-flaky material is used for micro-melting treatment, so that the micro-flaky material is stacked in layers to form a non-stick layer with a specific interlayer structure as above, and the interlayer structure formed not only has a large surface area, but also can provide gaps that are only conducive to the passage of water molecules and / or air. In this way, during the heating process of the cooker, the surface layer of the interlayer structure can capture and retain air and water vapor, and these gases expand when heated between the interlayers to form a good flotation effect between the interlayers, thereby reducing the direct contact between the food and the surface of the cooker and reducing the possibility of sticking to the pan. At the same time, the gaps in the surface layer of the interlayer structure do not allow oil molecules to pass through, that is, they can prevent oil molecules from passing through, thereby ensuring the stability of the flotation effect formed between the interlayers. This is because, on the one hand, if the oil molecules can pass through these interlayers, they will occupy the space originally belonging to the air and water vapor, thereby affecting the flotation effect, or inhibiting its formation. On the other hand, if the oil molecules can pass through the interlayer gaps, the oil molecules may adhere to the inner wall of the interlayer gaps, causing the interlayer gap structure to become blocked, thereby further destroying the air flotation effect and affecting the non-stick properties of the cookware. In this way, the cookware according to the present application has good initial non-stick properties and long-lasting non-stick properties.
[0027] In some embodiments, the step of slightly melting the surface of the micro-flaky material includes: heating the micro-flaky material with plasma, supersonic flame, electric arc or laser as an energy source to slightly melt the surface of the micro-flaky material.
[0028] In these embodiments, the non-stick layer can be adapted to pass through various types of heat sources, thereby broadening the methods of manufacturing the non-stick layer.
[0029] According to a third aspect of the present application, a non-stick cookware is provided, wherein the non-stick cookware comprises a substrate and a non-stick layer formed on the substrate, and the non-stick layer comprises the non-stick layer described above or comprises a non-stick layer manufactured by the method for manufacturing a non-stick layer described above.
[0030] In some embodiments, the non-stick cookware further includes a transition layer, which is formed of a metal material and is formed between the base and the non-stick layer.
[0031] In these embodiments, by providing a transition layer, the bonding force between the non-stick layer and the substrate can be further improved.
[0032] In some embodiments, the metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy. There are many materials for forming the transition layer, and a preference can be made based on manufacturing requirements. For example, when hardness needs to be improved at the same time, titanium alloy and iron alloy can be selected. The thickness of the transition layer is 8 microns to 80 microns. The transition layer can provide sufficient strength and adhesion without being too thick to affect the overall performance of the cooker. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The above and / or other features and aspects of the inventive concept will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings.
[0034] Figure 1 is a schematic diagram of a cross-sectional structure of a cooker provided in an embodiment of the present application after being cut along the thickness direction;
[0035] Figure 2 yes Figure 1 A schematic diagram of the enlarged structure at I in the middle;
[0036] Figure 3 is a scanning electron microscope image of a non-stick layer provided according to an embodiment of the present application;
[0037] Figure 4 is a schematic diagram of the structure of a non-stick layer provided according to an embodiment of the present application;
[0038] Figure 5 is a schematic diagram of a top view of a micron-scale scale provided according to an embodiment of the present application;
[0039] Figure 6 It is a schematic diagram of the side view structure of the micron-scale flakes provided according to an embodiment of the present application.
[0040] Explanation of symbols:
[0041] 100. non-stick cookware; 110. substrate; 120. non-stick layer; 130. transition layer; 10. micron-scale flakes; 11. nano-scale flakes. DETAILED DESCRIPTION
[0042] The exemplary embodiments of the inventive concept will be described in more detail below. Although the exemplary embodiments of the inventive concept are described below, it should be understood that the inventive concept can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided only to enable a more thorough understanding of the present invention and to enable the scope of the inventive concept to be fully communicated to those skilled in the art.
[0043] In this field, fluorine coating is a common material for forming non-stick cookware. However, although the non-stick layer made of fluorine coating has excellent initial non-stick properties, it is easily damaged by a spatula and is easily aged or decomposed due to high temperature during use. These problems have seriously affected the service life of the coating formed by the fluorine coating, resulting in the formation of the coating with general long-term non-stick properties. In addition, perfluoroalkyl and polyfluoroalkyl compounds (PFAS) are indispensable raw materials for the synthesis of fluorine coatings. As the industry's control over perfluoroalkyl and polyfluoroalkyl compounds (PFAS) becomes increasingly strict, it is an inevitable trend for fluorine coatings to withdraw from the stage of non-stick cookware. This also means that the materials that can be used for cookware coatings are gradually decreasing, so the development of new non-stick layers is still in urgent need in the field of cookware manufacturing.
[0044] At present, no material with lower surface energy than fluorine coating has been found, but the demand for non-stick in the cookware industry always exists, and ceramic coating is expected to replace fluorine coating. Ceramic coating is a liquid coating with silicone oil as the main non-stick component. Although the initial non-stick property of the coating formed by it is close to that of fluorine coating, as high-temperature cooking proceeds, the silicone oil will be continuously consumed due to the high temperature and quickly lose its non-stick effect. Therefore, the long-lasting non-stick property of ceramic coating cannot meet the demand for non-stick in cookware.
[0045] With the development of the non-stick industry, spray materials based on solid metal materials (for example, iron, stainless steel, low carbon steel, high carbon steel, cast iron and copper, etc.) or ceramic materials (for example, titanium oxide, titanium nitride, titanium carbide, ferrous iron tetroxide, iron oxide, ferrous oxide, aluminum oxide, chromium oxide and nickel oxide, etc.) have emerged, which can form a non-stick layer, namely the so-called "coating-free non-stick technology". The coating-free here is only to indicate that it does not use liquid organic coatings such as fluorine coatings or silicone coatings. Although the coating formed by the above-mentioned spraying materials is wear-resistant, the cookware with the coating only has the effect of cooking without sticking in the presence of oil, and its initial non-stickiness is poor, and it usually needs to be modified with materials with good non-stickiness, such as using polysiloxanes and fluorinated materials to modify it, in order to meet the initial non-stickiness required by the national standard. In addition, the non-stickiness of such materials decreases rapidly after wear, and the residual polysiloxane will have a counter-effect on the non-stickiness, and the non-stickiness is worse than before the modification.
[0046] As can be seen from the above, it is still difficult for existing non-stick cookware to achieve both initial non-stick and lasting non-stick properties. Therefore, developing new non-stick cookware with both initial non-stick and lasting non-stick properties plays an extremely important role in the field of cookware manufacturing.
[0047] The inventors have found that the gap structure of the non-stick layer can greatly affect the initial non-stickiness and lasting non-stickiness of the cookware. To this end, according to the inventive concept of the present application, a non-stick layer for cookware is provided, wherein at least the surface layer of the non-stick layer has a layer structure that can form an air flotation effect formed by a plurality of micro-scale flake materials (flakes) stacked on each other. Here, the layer structure is similar to a stack of fish scales, the micro-scale flake materials are micron-scale flakes, and each micron-scale flake is composed of a plurality of nano-scale flakes. Such micro-scale flake materials have a large surface area and a large number of interfaces, which can be conducive to forming a non-stick layer with a desired layer structure. Since the surface layer of the layer structure has a plurality of micron-scale gaps, and there are a plurality of nano-scale gaps between adjacent micron-scale gaps, the micron-scale gaps of the layer structure are further refined by the nano-scale gaps, so that the entire layer structure has a suitable gap size and a uniform gap distribution, and the gaps of the layer structure can only allow water molecules and / or air to pass freely, while effectively preventing oil molecules from penetrating, and the gap distribution of the layer structure can ensure the stability of the air flotation effect. When the cookware is heated, the air and water vapor on the surface of the interlayer structure form a significant flotation effect between the interlayers. This flotation effect forms a tiny air cushion between the food and the cookware, greatly reducing the direct contact and friction between the two, so that the cookware according to the present application has excellent initial non-stick performance and can maintain a lasting non-stick effect during long-term use.
[0048] According to a first aspect of the present application, a non-stick layer is provided, which is used in cookware and formed on a substrate of the cookware, wherein at least a surface layer of the non-stick layer has a layer gap structure, and the layer gap structure is formed by stacking a plurality of micro-flaky materials, and the micro-flaky materials are formed by stacking a plurality of nano-scale flakes, and the layer gap structure has a plurality of nano-scale gaps, and a plurality of micro-scale gaps are provided between adjacent nano-scale gaps.
[0049] In the embodiment of the present application, the micro-scale flaky material refers to a material having a similar scale shape and being micron-sized as a whole. As an example, the micro-scale flaky material is a micron-sized scale, wherein each micron-sized scale includes at least one layer, and each layer is composed of a plurality of nano-sized scales stacked. It is understood that each micron-sized scale is a primary structure, which also includes a secondary structure (multiple nano-sized scales) that is finer than the primary structure. Here, the primary structure can be regarded as the structure of a single scale macroscopically, and the secondary structure can be regarded as a component of the primary structure.
[0050] In some embodiments, the surface area of the micron-scale scale is 50 square microns-3600 square microns (the surface size of the scale is in the range of 7 microns-60 microns), and the thickness is 1 micron to 5 microns. The surface area of the nanoscale scale is about 1 / 9500-1 / 11000 of the surface area of the micron-scale scale, and the thickness of the nanoscale scale is about 1 / 90-1 / 110 of the thickness of the micron-scale scale. Here, it should be noted that the surface area of the micron-scale scale is the area of the entire outer surface of the micron-scale scale, that is, the sum of the areas of all external surfaces.
[0051] As an example, the surface area of the nanoscale flakes is 4900 square nanometers to 360,000 square nanometers (the size of the nanoscale flakes is 70 nanometers to 600 nanometers), and the thickness is 10 nanometers to 50 nanometers. Here, it should be noted that the surface area of the nanoscale flakes is the area of the entire outer surface of the nanoscale flakes, that is, the sum of the areas of all external surfaces.
[0052] As some examples, the micro-scale material is a single layer of micron-scale scales, and each micron-scale scale is composed of a plurality of scales of smaller sizes. Specifically, each micron-scale scale is composed of a plurality of stacked nanoscale scales.
[0053] As some other examples, the micro-scale material is a multi-layer micron-scale scale, each layer of which is composed of a plurality of scales of a smaller size. Specifically, each layer of the multi-layer micron-scale scale is composed of a plurality of stacked nanoscale scales.
[0054] In these embodiments, the preparation method of the single-layer micro-flaky material is simple, and the multi-layer micro-flaky material can have relatively better properties, such as strength, toughness or corrosion resistance.
[0055] In summary, according to the present application, the micro-scale flaky material can have a suitable surface area and number of interfaces, so that a non-stick layer with a desired lamellar structure can be formed by stacking the flaky material in layers.
[0056] In the embodiment of the present application, at least the surface layer of the non-stick layer has a layer gap structure, which is intended to illustrate that the layer gap structure is not limited to the surface layer of the non-stick layer, but can be extended to the entire structure of the non-stick layer. That is, the non-stick layer has a layer gap structure from one side to the other side in the thickness direction. The criss-cross layer gap structure is formed by stacking micro-scale flaky materials in layers.
[0057] According to the non-stick layer provided by the embodiment of the present application, a plurality of micro-scale-like materials can form a criss-cross interlayer structure (similar to the stack formed by the arrangement of fish scales) by stacking, and the interlayer structure formed not only has a large surface area, but also can provide a gap that is only conducive to the passage of water molecules and / or air. In this way, during the heating process of the cooker, the surface layer of the interlayer structure can capture and retain air and water vapor, and these gases expand when heated between the interlayers to form a good flotation effect between the interlayers, thereby reducing the direct contact between the food and the surface of the cooker and reducing the possibility of sticking to the pan. At the same time, the gaps in the surface layer of the interlayer structure do not allow oil molecules to pass through, that is, oil molecules can be prevented from passing through, so that the stability of the flotation effect formed between the interlayers can be ensured. This is because, on the one hand, if the oil molecules can pass through these interlayers, then they will occupy the space originally belonging to air and water vapor, thereby affecting the flotation effect, or inhibiting its formation. On the other hand, if the oil molecules can pass through these interlayers, then the oil molecules may adhere to the inner wall of the interlayer, causing the interlayer structure to become blocked, thereby further destroying the flotation effect and affecting the non-stickiness of the cooker. Thus, the cookware according to the present application has good initial non-stick properties and long-lasting non-stick properties.
[0058] According to the present application, the micro-scale flake material is a micron-scale flake, which is itself formed by stacking a plurality of nano-scale flakes, and adjacent nano-scale flakes are stacked in an alternating manner to form a micron-scale flake.
[0059] Figure 5 It is a schematic diagram of the top view structure of the micron-scale flakes provided according to the embodiment of the present application. Figure 6 is a schematic diagram of the side view structure of the micron-scale flakes provided in the embodiment of the present application. Figure 5 As shown, a micron-scale scale 10 is composed of a plurality of nano-scale scales 11. Specifically, adjacent nano-scale scales 11 are stacked in layers to form a micron-scale scale 10. Figure 6 As shown, it can be seen that the micron-sized scales 10 having a multi-layer structure are arranged in layers in the thickness direction thereof.
[0060] In some embodiments, the surface area of the micron-scale flakes is 50 square microns to 3600 square microns (the surface size of the flakes is in the range of 7 microns to 60 microns) and the thickness is 1 micron to 5 microns.
[0061] In these embodiments, micron-scale flakes with a specific surface area and thickness can effectively micro-melt and accumulate to form a non-stick layer under the action of a subsequent energy source, matching with the subsequent energy source, thereby facilitating the optimal performance of the non-stick layer.
[0062] In some embodiments, among the micron-scale flakes, the surface area of the nano-scale flakes is 4900 square nanometers to 360000 square nanometers, and the thickness is 10 nanometers to 50 nanometers. In this way, micron-scale flakes with predetermined gaps can be constructed so that the non-stick layer formed by the micron-scale flakes has a desired layer gap structure, thereby paving the structure for forming an air flotation effect to enhance the non-stickiness of the non-stick layer.
[0063] In some embodiments, in the micro-scale flaky material, the gap between adjacent nano-scale flakes is in the range of 50 nanometers to 200 nanometers, and the micro-scale flakes formed by the nano-scale flakes with such gaps are used as micro-scale flaky materials. Since the gaps inside the micro-scale flaky materials are retained to a great extent during the formation of the non-stick layer, the nano-scale gaps in the formed interlayer structure can be guaranteed, so that the desired interlayer structure can be obtained. Here, the retention of the gaps in the micro-scale flaky materials is very important for the desired gap structure. This is because the presence of nano-scale gaps not only increases the surface area of the interlayer structure, but also provides more gas channels, which helps to form a more uniform and stable flotation effect. At the same time, the combination of micro-scale gaps and nano-scale gaps forms a multi-level microstructure, which can more effectively reduce the direct contact area between the coating and the contacting substance, thereby reducing adhesion.
[0064] According to the present application, the micro-scale flaky material is an inorganic non-metallic material having a certain hardness and high temperature resistance, so that the formed non-stick layer can remain stable under high temperature and wear environment.
[0065] In some embodiments, the inorganic non-metallic material is an oleophilic material, so that it is possible to facilitate the subsequent formation of a fatty acid salt modified layer on its surface. As an example, the inorganic non-metallic material includes mica iron oxide or a modified form of mica iron oxide. Here, mica iron oxide is not a simple mixture of mica and iron oxide, but an iron ore with ferric oxide (Fe2O3) as the main chemical component. The above materials have low surface energy and high wear resistance, which can ensure that the non-stick layer formed therefrom has a certain degree of durability. In a preferred embodiment, the mica iron oxide is gray mica iron oxide, which can ensure that the formed non-stick layer has a relatively dark color, thereby enhancing the product's resistance to dirt and user experience.
[0066] According to the present application, in the non-stick layer, the interlayer structure has a plurality of micrometer-scale gaps, and a plurality of nanometer-scale gaps are provided between adjacent micrometer-scale gaps.
[0067] Figure 3 is a scanning electron microscope image of the non-stick layer provided according to an embodiment of the present application. Figure 4 Schematic diagram of the structure of the non-stick layer provided according to the embodiment of the present application. Figure 3 and Figure 4It can be roughly seen that adjacent micro-scale flaky materials are stacked in layers to form a non-stick layer with a fish-scale-like interlayer structure, and it can be seen that the interlayer structure has large gaps (micrometer-level gaps) and small gaps (nanoscale gaps).
[0068] The inventors have also found that the gap size and gap distribution in the layer gap structure can greatly affect the uniformity of the air floating effect in forming the non-stick layer.
[0069] According to the present application, the interlaminar structure has gaps of multiple levels of size, which are smaller than the size of the micro-scale material, about 1 / 5-1 / 7 of the size of the micro-scale material. In the non-stick layer, the interlaminar structure has not only micron-level gaps, but also nano-level gaps, and there are multiple nano-level gaps between adjacent micron-level gaps, so that in the non-stick layer, nano-level gaps and micron-level gaps can be combined to form a multi-level microstructure. Among them, the micron-level gap will help reduce the direct contact area between the coating and the contact material, thereby reducing the adhesion. The nano-level gap may play a fine-tuning role, refine the distribution of the entire gap, and improve the uniformity of the gap distribution, thereby further enhancing the non-stick performance by improving the uniformity of the flotation effect. Here, the flotation effect is formed by the heat expansion of air and water vapor in the non-stick layer during the heating process. It can form a layer of "air cushion" between the coating and the contact material, further reducing the direct contact between them. The introduction of nano-level gaps makes the flotation effect more uniform and stable, thereby further enhancing the non-stick performance.
[0070] In addition, gaps of different sizes also play a role in regulating and dispersing stress. During the cooking process, cookware is subject to various external forces, such as temperature changes, food pressure, etc. These external forces may cause stress concentration and damage inside the coating. The multi-level and multi-scale gap structure design can effectively disperse these stresses and reduce the impact of stress on the coating, thereby improving the stability and durability of the non-stick layer.
[0071] In some embodiments, the nano-scale gap is 1 / 45-1 / 55 of the micro-scale gap. As an example, the size of the micro-scale gap is 1 micron-10 microns, and the size of the nano-scale gap is 50 nanometers-200 nanometers.
[0072] In these embodiments, the non-stick layer having a layer gap structure with both micrometer-scale gaps and nanometer-scale gaps of the above sizes has a higher uniformity of the layer gap structure and a more significant air flotation effect, and can have improved initial non-stickiness and lasting non-stickiness.
[0073] In some embodiments, the micron-scale gap and the nano-scale gap are irregular shapes. Compared with regular gap structures, irregular shapes can provide more surface changes and spatial distributions, which help gases (such as air and water vapor) to be more evenly distributed and expanded in the gaps, thereby enhancing the stability and uniformity of the air flotation effect. Preferably, the irregular shape is a meniscus-shaped gap, which is conducive to forming a uniform and stable air flotation effect, because the meniscus shape has an attractive force and can guide the gas to flow along its curved surface, thereby further enhancing the stability and uniformity of the air flotation effect.
[0074] In some embodiments, the thickness d2 of the non-stick layer is 10 micrometers to 150 micrometers. In this way, the properties of the cookware in terms of weight, non-stickiness, thermal conductivity, etc. can be balanced, so that the overall performance of the cookware is better.
[0075] In some embodiments, the hardness of the non-stick layer is 600 HV to 1100 HV. The non-stick layer of such hardness can balance wear resistance and flexibility. It has sufficient wear resistance to resist scratches and abrasion, while maintaining good flexibility to avoid cracking or peeling under temperature changes or mechanical stress.
[0076] In some embodiments, the non-stick layer has a temperature tolerance of 800° C.-1200° C. Thus, the cookware having the non-stick layer is not afraid of high temperatures and has longer durability.
[0077] In some embodiments, the surface energy of the non-stick layer is 28 mN / m-34 mN / m, so that the cookware with the non-stick layer can have good initial non-stick properties.
[0078] According to other embodiments of the present application, the non-stick layer includes a plurality of sub-layers stacked in the thickness direction of the non-stick layer, and the interlayer structures of the sub-layers are arranged in a staggered manner in the thickness direction of the non-stick layer. There are gaps between adjacent micro-scale materials in each sub-layer. On the one hand, the gaps in the surface layer of the non-stick layer can allow water molecules and / or air to pass through and prevent oil molecules from passing through, which is similar to the stacking method of fish scales, and has a gap size and gap distribution that is convenient for forming an air flotation effect. On the other hand, the probability of forming through holes in the thickness direction of the non-stick layer as a whole is small, which can improve the corrosion resistance of the non-stick layer to a certain extent.
[0079] According to the present application, the non-stick layer can further improve the non-stick property by means of two principles. Specifically, when grease contacts the non-stick layer, an oil film layer is easily formed on the surface of the non-stick layer to further optimize the non-stick property of the cookware.
[0080] According to some embodiments of the present application, a fatty acid salt modified layer is connected to the surface of the non-stick layer, wherein the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the non-stick layer.
[0081] In some embodiments, the oil comprises at least one of stearin, palmitin, and olein.
[0082] In these embodiments, a fatty acid salt modified layer is further connected to the surface of the non-stick layer. The fatty acid salt modified layer is compatible with oils and fats. Therefore, by utilizing the oil film non-stick principle, the initial non-stick property and the lasting non-stick performance of the cookware are improved to a certain extent.
[0083] According to a second aspect of the present application, a method for manufacturing a non-stick layer is provided, wherein the method for manufacturing the non-stick layer comprises:
[0084] Step S102, providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes.
[0085] Step S103, micro-melting the surface of the micro-scale flaky material, so as to form a non-stick layer having a layer structure with a plurality of micron-scale gaps by stacking the micro-scale flaky material, wherein a plurality of nano-scale gaps are provided between adjacent micron-scale gaps.
[0086] According to the method for manufacturing a non-stick layer provided in an embodiment of the present application, a specific micro-flaky material is used for micro-melting treatment, so that the micro-flaky material is stacked in layers to form a non-stick layer with a specific interlayer structure as above, and the interlayer structure formed not only has a large surface area, but also can provide gaps that are only conducive to the passage of water molecules and / or air. In this way, during the heating process of the cooker, the surface layer of the interlayer structure can capture and retain air and water vapor, and these gases expand when heated between the interlayers to form a good flotation effect between the interlayers, thereby reducing the direct contact between the food and the surface of the cooker and reducing the possibility of sticking to the pan. At the same time, the gaps in the surface layer of the interlayer structure do not allow oil molecules to pass through, that is, they can prevent oil molecules from passing through, thereby ensuring the stability of the flotation effect formed between the interlayers. This is because, on the one hand, if the oil molecules can pass through these interlayers, they will occupy the space originally belonging to the air and water vapor, thereby affecting the flotation effect, or inhibiting its formation. On the other hand, if the oil molecules can pass through the interlayer gaps, the oil molecules may adhere to the inner wall of the interlayer gaps, causing the interlayer gap structure to become blocked, thereby further destroying the air flotation effect and affecting the non-stick properties of the cookware. In this way, the cookware according to the present application has good initial non-stick properties and long-lasting non-stick properties.
[0087] The specific method for manufacturing the non-stick layer can be understood in conjunction with the method for manufacturing the cooker in the following embodiment.
[0088] According to a third aspect of the present application, a method for manufacturing a cooker is provided, wherein the method for manufacturing the cooker comprises:
[0089] Step S101, providing a substrate.
[0090] Step S102, providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes.
[0091] Step S103, micro-melting the surface of the micro-scale flaky material, so as to form a non-stick layer having a layer structure with a plurality of micron-scale gaps by stacking the micro-scale flaky material, wherein a plurality of nano-scale gaps are provided between adjacent micron-scale gaps.
[0092] Hereinafter, the method for manufacturing the cooker of the present application will be described in detail with reference to specific embodiments.
[0093] Provide substrate
[0094] According to the present application, the substrate 110 can be made of commonly used materials or a composite of multiple materials. For example, the material can be stainless steel, titanium, aluminum, titanium alloy or aluminum alloy. The substrate 110 can have a shape corresponding to the function, for example, Figure 1 As shown in FIG. 1 , when the non-stick cookware 100 is a non-stick pan, the base 110 may have a conventional pan shape. It should be understood that Figure 1 Only the main body of the non-stick pan is exemplarily shown without showing other parts, and the non-stick pan according to the present invention may also include common cookware structures / components such as a handle (eg, a pot handle).
[0095] According to the present application, the substrate 110 may be pre-treated, for example, grinding, sandblasting, pickling, etc. The substrate 110 has a certain surface roughness, and in an exemplary embodiment, the surface roughness Ra value may be in the range of 3 μm-5 μm.
[0096] In some embodiments, the thickness d1 of the substrate may be in the range of 1.0 mm to 2.5 mm.
[0097] Forming a transition layer (optional)
[0098] According to the present application, a metal material is thermally sprayed to form a transition layer, wherein the spraying method can adopt an existing process for forming a layer. As an example, the spraying method is cold spraying or plasma spraying. In a preferred embodiment, the spraying method is plasma spraying, and the spraying parameters include current, voltage, main gas flow rate, hydrogen flow rate, powder feeding gas flow rate, powder feeding amount, etc. Specifically, the current is 200A-300A; the voltage is 30V-50V; the main gas (argon) flow rate is 1500L / h-2000L / h; the hydrogen flow rate is 40L / h-60L / h; the powder feeding gas flow rate is 25L / h-40L / h; the powder feeding amount is 15g / min-25g / min; the spraying (the distance from the gun nozzle to the workpiece) distance is 15cm-25cm; the spraying angle is 45°-80°; the workpiece temperature is 15℃-25℃.
[0099] In some embodiments, the metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy. As an example, the iron alloy can be stainless steel. By thermally spraying the above metal materials to form a transition layer of the cooker, a transition layer with a certain rough surface can be formed on the substrate, thereby improving the bonding force between the non-stick layer and the substrate thereon. In addition, the selection of the metal material can be selected based on the need for tendency. For example, when it is necessary to improve the heating efficiency of the cooker, aluminum with good thermal conductivity can be used as the material for forming the transition layer to improve the heating efficiency by improving the thermal conductivity of the cooker.
[0100] In some embodiments, the metal material is in a granular form. As an example, the particle size of the metal material is between 10 microns and 60 microns, so that it can meet the process requirements of plasma spraying, have good powder feeding fluidity and heat melting properties, and form a transition layer with a preset rough surface. As an example, the shape of the metal material can be spherical or quasi-spherical, so that a relatively dense transition layer can be formed through the principle of spherical close packing to improve thermal conductivity and corrosion resistance.
[0101] In some embodiments, the thickness of the transition layer is 8 micrometers to 80 micrometers. If the thickness of the transition layer is too thin, it is easy to be uneven locally, and the desired rough surface cannot be formed, and the role of the transition layer cannot be played. If the thickness of the transition layer is too thick, a large stress will be generated, resulting in a decrease in bonding strength.
[0102] In some embodiments, the roughness of the surface of the transition layer is 3 micrometers to 6 micrometers. Such roughness can ensure the bonding strength of the non-stick layer thereon.
[0103] Forming a non-stick layer
[0104] According to the present application, the step of forming a non-stick layer includes micro-melting the surface of the micro-flaky material to form a non-stick layer with a layer structure having multiple micron-sized gaps by stacking the micro-flaky material, wherein there are multiple nano-sized gaps between adjacent micron-sized gaps.
[0105] In these embodiments, the surface of the micro-flaky material is slightly melted, which enables the micro-flaky material to be connected to the substrate without damaging the internal structure of the micro-flaky material. In this way, the internal structure of the micro-flaky material can be retained in the non-stick layer to a large extent, thereby forming a laminar structure of the non-stick layer to improve the non-stick performance.
[0106] According to the present application, the step of forming the non-stick layer includes the step of preparing a micro-scale material.
[0107] According to the present application, the micro-scale flaky material is an inorganic non-metallic material. The inorganic non-metallic material includes micaceous iron oxide or a modified product of micaceous iron oxide. Here, micaceous iron oxide is not a simple mixture of mica and iron oxide, but an iron ore with ferric oxide (Fe2O3) as the main chemical component. It should be noted that it also contains other elements such as potassium, aluminum, lithium, and magnesium, but its core component is α-Fe2O3. Its crystals are hexagonal in the form of flakes or plates.
[0108] In some embodiments, the micro-flaky material includes, in terms of main components, iron oxide, silicon dioxide, aluminum oxide, potassium oxide, ferroferric oxide, calcium oxide, sodium oxide, magnesium oxide, manganese oxide and titanium oxide, and in terms of weight percentage, 30%≤iron oxide≤50%, 15%≤silicon dioxide≤30%, 4%≤aluminum oxide≤20%, 30%≤potassium oxide≤40%, 0.01%≤ferroferric oxide≤0.08%, 0.08%≤calcium oxide≤0.13%, 0.01%≤sodium oxide≤0.05%, 0.2%≤magnesium oxide≤0.35%, 0.02%≤manganese oxide≤0.13% and 0.21%≤titanium oxide≤0.33%.
[0109] In the embodiment of the present application, iron oxide (Fe2O3) is one of the main components of the micro-scale flaky material, and the weight of iron oxide is between 30% and 50%. Iron oxide not only has anti-rust properties, but also increases the hardness and wear resistance of the micro-scale flaky material. At the same time, iron oxide has good oleophilic properties, and can be very good at rusting and grease affinity, providing certain non-stick properties for cookware. The content of silicon dioxide (SiO2) is between 15% and 30%, which can improve the thermal stability and chemical stability of the micro-scale flaky material. The weight of aluminum oxide (Al2O3) is between 4% and 20%, which can enhance the hardness and wear resistance of the micro-scale flaky material. The weight of potassium oxide (K2O) is between 30% and 40%, and potassium oxide can be used to adjust the conductivity of the micro-scale flaky material or improve its compatibility with other components, and can also reduce the melting point of the micro-scale flaky material, which is convenient for good micro-melting when preparing the non-stick layer. The weight percentage of ferroferric oxide (Fe3O4) is between 0.01% and 0.08%, which is used to fine-tune the magnetic or electromagnetic properties of the material. It also has a black appearance, which can deepen the blackness of the material and improve the anti-fouling performance of the non-stick layer. The weight percentage of calcium oxide (CaO) is between 0.08% and 0.13%, which is used to adjust the pH value of the material or as an alkaline component, which helps to improve the corrosion resistance of the micro-scale material; at the same time, calcium ions can form a modified layer of fatty acid salts with grease to provide certain non-stick properties. The weight percentage of sodium oxide (Na2O) is between 0.01% and 0.05%, which is used to adjust the conductivity or compatibility of the material; alkaline metal oxides can also reduce the melting point of the micro-scale material, making it easy to form a micro-melting state when heated. The weight percentage of magnesium oxide (MgO) is between 0.2% and 0.35%, which helps to improve the fire resistance of the micro-scale material; at the same time, magnesium ions can also form fatty acid salts with grease to provide non-stick properties. The weight percentage of manganese oxide (MnO) is between 0.02% and 0.13%, which is used to improve the color of the micro-scale material, ensure that the color of the non-stick layer formed is relatively dark, improve the dirt resistance, and ensure user experience. The weight percentage of titanium oxide (TiO2) is between 0.21% and 0.33%, which can improve the whiteness and hiding power of the micro-scale material, and at the same time has certain photocatalytic properties, which helps to improve the antibacterial properties of the material.
[0110] In these embodiments, the micro-scale material having the above ingredients is an inorganic non-metallic material with excellent rust resistance, high hardness and wear resistance, and low surface energy, so that the properties of the formed non-stick layer are better in all aspects.
[0111] According to the present application, the step of preparing the micro-scale flaky material may also include the step of manufacturing the micro-scale flaky material.
[0112] In some embodiments, the micro-scale flaky material is mica iron oxide, and the mica iron oxide can be obtained by using the specularite associated with mica ore as a raw material. Specifically, the ground specularite is reacted with an acid (for example, a sulfuric acid solution with a mass concentration of 10%) in a mass ratio of 40:60 to dissolve the iron element therein and remove impurities. Then, an oxidant (such as chlorine, oxygen, etc.) is added to the solution to oxidize the ferrous ions into ferric ions. An alkali (such as caustic soda) is added to neutralize the solution so that the iron ions are precipitated in the form of ferric hydroxide. Finally, the precipitate is subjected to hydrothermal treatment (such as treatment in an autoclave), and the ferric hydroxide is converted into mica iron oxide by controlling conditions such as temperature, pressure and reaction time. Finally, the micro-scale flaky material of the desired size is obtained by screening.
[0113] In other embodiments, the micro-scale material is mica iron oxide, which can be obtained by high-temperature vacuum pyrolysis. Specifically, mica and iron salt are evenly mixed in a weight ratio of 60:40, and then the mixed raw materials are pyrolyzed under vacuum conditions of 1100°C-1300°C. In this process, the iron salt decomposes to generate iron oxide, and combines with mica to form mica iron oxide powder. As an example, the iron salt may include ferric chloride and ferric sulfate.
[0114] In some other embodiments, the micro-scale material is mica iron oxide, which can be obtained by the iron oxide sol method. Specifically, ferric chloride or ferric sulfate is selected as the iron source, sodium hydroxide solution is used as the alkali source, and mica aqueous suspension is used as the carrier. Then, ferric chloride or ferric sulfate and sodium hydroxide solution are mixed in a weight ratio of 15:85, and then quickly added to a mica aqueous suspension with a mass concentration of 20%. Then, under appropriate temperature and pressure, a hydrothermal reaction is carried out to combine iron ions with mica to form mica iron oxide. Finally, after the reaction is completed, post-processing steps such as washing, drying and grinding are carried out to obtain the final mica iron oxide powder.
[0115] According to the present application, the mica iron oxide according to the present application can be obtained as a micro-scale flaky material by the above three methods. The mica iron oxide has a micro-scale flaky material with a desired structure, and the iron oxide in the mica iron oxide is α-Fe2O3, has a specific crystal structure, has a large diameter-thickness ratio, a size between 7 microns and 60 microns, and a thickness of 1 micron to 5 microns. This flaky structure enables the mica iron oxide to form a dense coating, so that the non-stick layer also has certain anti-corrosion properties. In the present application, the weight ratio of mica to iron oxide in the micro-scale flaky material is (30-60): (40-70).
[0116] According to the present application, the preparation method of the modified mica iron oxide includes first adding 40-50 parts of mica iron oxide to 60-70 parts of an aqueous solution containing 0.8% stearic acid by mass concentration, then placing it in an ultrasonic water bath at 60°C-70°C for heating, stirring and ultrasonic treatment for 0.5h-1h, and then drying with hot air below 100°C to obtain mica iron oxide with a stearic acid modified layer on the surface. Of course, according to the present application, other similar modifiers can also be used to modify mica iron oxide to obtain a modified mica iron oxide.
[0117] According to the present application, the step of slightly melting the surface of the micro-scale material includes plasma spraying the micro-scale material with preset parameters so that the surface of the micro-scale material is slightly melted.
[0118] In some embodiments, causing the surface of the micro-scale material to slightly melt includes: heating the micro-scale material with plasma, supersonic flame, arc or laser as an energy source to cause the surface of the micro-scale material to slightly melt.
[0119] As an example, the preset parameters of plasma include current of 350A-650A; voltage of 50V-85V; main gas (argon) flow rate of 1000L / h-2000L / h; hydrogen flow rate of 60L / h-80L / h; powder feeding gas flow rate of 35L / h-50L / h; powder feeding amount of 25g / min-35g / min; spraying (distance from gun nozzle to workpiece) distance of 15cm-20cm; spraying angle of 45°-80°; workpiece temperature of 15℃-25℃.
[0120] As an example, the preset parameters of supersonic flame spraying include a fuel flow rate in the range of 24L / h to 30L / h, an oxygen flow rate in the range of 51.7m3 / h to 56m3 / h, a powder supply rate in the range of 1.4g / min to 70.0g / min, and a spraying distance between 300mm and 380mm to obtain the best spraying effect.
[0121] As an example, the preset parameters of arc spraying include: spraying current is 150A-180A; spraying voltage is 30V-32V; spraying pressure is 0.45MPa-0.55MPa; spraying distance is 100mm-120mm.
[0122] As an example, the preset parameters of laser cladding include laser power of 3KW-4KW, circular or rectangular spot can be selected, the spot is 3mm-5mm away from the workpiece surface, the laser cladding line speed is 20m / min-50m / min, and nitrogen or argon is used as the protective gas.
[0123] According to other embodiments of the present application, the non-stick layer includes a plurality of sub-layers stacked together, and the layer gap structures of the respective sub-layers are arranged alternately in the thickness direction of the non-stick layer. In the corresponding manufacturing method, the non-stick layer is formed in multiple times, so that the layer gap structures of the respective sub-layers are arranged alternately in the thickness direction of the non-stick layer, so as to reduce the porosity and improve the corrosion resistance.
[0124] In the present application, the size of the micro-flaky material of each sub-layer forming the non-stick layer can be set so that each sub-layer is formed by micro-flaky material of different sizes, so that the layer gap structure of each sub-layer is arranged alternately in the thickness direction of the non-stick layer.
[0125] As an example, the size of the micro-scale material forming the relatively inner layer can be relatively larger, and the size of the micro-scale material forming the relatively outer layer can be relatively smaller, or the size of the micro-scale material forming the relatively inner layer can be relatively smaller, and the size of the micro-scale material forming the relatively outer layer can be relatively larger, so that the gaps between the sub-layers of the non-stick layer formed can be staggered in the thickness direction, so that the gaps between the sub-layers of the non-stick layer in the thickness direction can not communicate with each other, so that it can act as a barrier layer to prevent the entry of corrosive media, avoid corrosion of the junction between the substrate and the non-stick layer, and ensure the rust resistance of the product with the non-stick layer. It should be noted that in these embodiments, when the size of the material located on the outside is smaller, it can also inhibit the entry of corrosive media (for example, water molecules), and the rust prevention effect is relatively better.
[0126] In some embodiments, the non-stick layer includes multiple sublayers stacked in the thickness direction, the innermost layer of the multiple sublayers is used to connect with the base of the cookware, and the outermost layer of the multiple sublayers is used as the inner surface of the cookware, wherein the micro-scale material includes a plurality of first micron-sized scales and a plurality of second micron-sized scales, wherein the surface area of the first micron-sized scales is greater than the surface area of the second micron-sized scales, and the thickness of the first micron-sized scales is greater than the thickness of the second micron-sized scales.
[0127] As some examples, a first sublayer is formed on a substrate with a first micron-sized scale, and then a second sublayer is formed on the first sublayer with a second micron-sized scale, so that the interlayer structures of the sublayers of the non-stick layer are arranged alternately in the thickness direction of the non-stick layer.
[0128] As some other examples, a first sublayer is formed on a substrate with a second micron-sized scale, and then a second sublayer is formed on the first sublayer with a first micron-sized scale, so that the interlayer structures of the sublayers of the non-stick layer are arranged alternately in the thickness direction of the non-stick layer.
[0129] In these embodiments, with the same spraying parameters, the smaller micron-sized flakes can be arranged more closely together to form a relatively dense sublayer. This dense structure helps to reduce the penetration path of the corrosive medium and improve the anti-corrosion performance of the non-stick layer. On the contrary, the larger micron-sized flakes will form a relatively loose sublayer when sprayed. When two different sublayers are stacked in the thickness direction, their gaps tend to be arranged in a staggered manner along the thickness direction of the non-stick layer. This staggered arrangement helps to form a complex interlayer structure, further increasing the difficulty of corrosive medium penetration. In addition, the uniformity of the surface pore distribution can be ensured by the staggered interlayer structure, and the pressure of the corrosive medium can be more effectively dispersed to prevent it from concentrating in a specific area and causing the failure of the non-stick layer.
[0130] In some embodiments, the surface area of the first micron-scale scale is 50 square microns-1000 square microns, and the thickness is 1 micron to 3 microns, and the surface area of the second micron-scale scale is 1000 square microns-3600 square microns, and the thickness is 3 microns to 5 microns. More specifically, the first micron-scale scale is composed of a plurality of first nanoscale scales stacked, the surface area of the first nanoscale scale is 4900 square nanometers-90000 square nanometers, and the thickness is 10 nanometers to 30 nanometers; and / or the second micron-scale scale is composed of a plurality of second nanoscale scales stacked, the surface area of the second nanoscale scale is 90000 square nanometers-360000 square nanometers, and the thickness is 30 nanometers to 50 nanometers. The above size form can facilitate the formation of a non-stick layer with a layer structure in which the gaps between the sub-layers in the thickness direction of the non-stick layer are not connected to each other.
[0131] Forming oil film
[0132] According to the present application, before the step of forming the oil film layer, the non-stick layer may be polished and ground to make the surface bright and smooth, which is convenient for subsequent stir-frying operations.
[0133] According to the present application, the non-stick layer can achieve non-stickiness by means of the air flotation effect, and can also achieve non-stickiness by means of the oil film principle. Thus, by optimizing the non-stickiness of the non-stick layer through the two non-stick principles, excellent non-stick performance can be obtained.
[0134] At present, compared with the oil film layer formed by physical bonding, the bonding force between the chemically bonded oil film modification layer and the substrate is strong, and the oil film layer itself has high hardness and wear resistance, so it can maintain its non-stickiness for a long time during use. Even if it is affected by external factors such as high temperature and grease during use, the oil film layer is not easy to deteriorate or fail. This makes the chemically bonded oil film modification layer show better performance in terms of long-lasting non-stickiness. The acidity of grease is weak, and the ions on the surface of the substrate are mostly in atomic state, so it is impossible to form chemical bonds through acid-base reactions. On the contrary, it tends to bind to the metal surface through physical adsorption or weak chemical adsorption.
[0135] According to the present application, the oil is at least one of stearic acid glyceryl, palmitic acid glyceryl and oleic acid glyceryl, and the oil is brought into contact with the treated non-stick layer, and a modified layer is formed on the surface of the non-stick layer through chemical bonding. These modified layers will further optimize the non-stick properties of the cookware with the help of the oil film non-stick principle.
[0136] According to the present application, the method for manufacturing the cookware also includes oxidizing the substrate to form an oxide film on its surface. This oxide film not only improves the activity of the metal surface, but also provides a reaction site for the subsequent grafting of fatty acid salts. The oxidation treatment method may include micro-arc oxidation, anodizing, gas oxidation, etc., and the specific selection depends on the material of the substrate and the required performance. The 0-valent metal atoms on the surface of the substrate are oxidized into high-valent metal ions to increase the activity of the metal surface and facilitate subsequent chemical bonding with fatty acids. At the same time, the metal oxide film has a high hardness and can enhance the durability of the non-stick layer.
[0137] Specifically, an appropriate oxidation treatment method is selected, such as micro-arc oxidation, anodic oxidation, gas oxidation and salt bath oxidation, etc. For aluminum and its alloys, micro-arc oxidation or anodic oxidation is preferred; for stainless steel, gas oxidation is preferred.
[0138] According to the present application, the manufacturing method of the cooker also includes a hydration treatment after the substrate has been subjected to a preliminary oxidation treatment. Specifically, after the oxidation treatment, a layer of oxide film will be formed on the surface of the non-stick layer. In order to improve the activity of the oxide film, water vapor can be used to perform a hydration oxidation treatment on it. Water vapor reacts with metal oxides to generate hydrated oxides. During this process, the oxide film will expand in volume and produce a large number of hydroxyl groups (-OH). These hydroxyl groups are highly active functional groups and are easy to react with other compounds. When combined with fatty acids, these hydroxyl groups can undergo an esterification reaction with the carboxyl group (-COOH) in the fatty acid. Esterification is a chemical reaction that forms ester compounds, in which the carboxyl group combines with the hydroxyl group to form an ester bond (-COO-) and water.
[0139] Specifically, the non-stick layer is a mica iron oxide layer, which can contain calcium and magnesium metal ions after oxidation and water vapor treatment. The oil contains free fatty acids, and the carboxyl groups in the fatty acids can combine with calcium and magnesium ions to form fatty acid calcium or fatty acid magnesium, which are then deposited and attached to the surface of the non-stick layer to form fatty acid salts.
[0140] According to some embodiments of the present application, a fatty acid salt modified layer is connected to the surface of the layer gap structure, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the non-stick layer.
[0141] In these embodiments, by performing oxidation treatment and water vapor treatment on the inner surface of the substrate, a hydrated oxide film containing water and oxides can be generated on the surface of the non-stick layer. This film can not only seal the pores in the oxide film, improve the compactness and corrosion resistance of the substrate, but also produce a large number of hydroxyl groups, providing reaction sites for the esterification reaction with fatty acids. Through the esterification reaction, a strong chemical bond is formed between the fatty acid and the substrate, thereby further improving the adhesion and durability of the oil film layer.
[0142] In some embodiments, the thickness of the fatty acid salt modified layer is 0.08 micrometers to 0.12 micrometers. Such a thickness can be maintained for a long time to improve the non-stick property of the cookware.
[0143] According to a fourth aspect of the present application, a cooking utensil is provided, wherein: Figure 1 and Figure 2 As shown, the cookware includes a base 110 and a non-stick layer 120 formed on the base, and the non-stick layer 120 includes the non-stick layer provided according to the above embodiment.
[0144] In some embodiments, the cookware further includes a transition layer 130 formed of a metal material and formed between the base and the non-stick layer.
[0145] In these embodiments, by providing a transition layer, the bonding force between the non-stick layer and the substrate can be further improved.
[0146] In some embodiments, the metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy. There are many materials for forming the transition layer, and a preference can be made based on manufacturing requirements. For example, when hardness needs to be improved at the same time, titanium alloy and iron alloy can be selected. The thickness of the transition layer is 8 microns to 80 microns. The transition layer can provide sufficient strength and adhesion without being too thick to affect the overall performance of the cooker.
[0147] The present application will be described in detail below in conjunction with specific embodiments, but the protection scope of the present application is not limited to the embodiments.
[0148] Example 1
[0149] The cookware according to Example 1 was manufactured by the following method.
[0150] Step S10, preparing a cookware base. Specifically, the step of preparing the cookware base includes deep drawing the aluminum alloy, alkali washing and degreasing the surface, drying, and sandblasting, thereby obtaining an aluminum cookware base with a thickness of 1.5 mm as the cookware base.
[0151] Step S20, performing sandblasting on the inner surface of the cookware base to control the roughness of the inner surface within a range of 4 microns.
[0152] Step S30, using titanium particles with an average particle size of 10 microns to form a transition layer with a thickness of 30 microns and a roughness of 8 microns on the inner surface of the aluminum pot substrate by plasma spraying technology. The parameters of the plasma spraying process are: current of 250A, voltage of 40V, main gas (argon) flow rate of 1700L / h, hydrogen flow rate of 50L / h, powder feeding gas flow rate of 30L / h, powder feeding amount of 20g / min, spraying distance of 20cm, spraying angle of 40°, and workpiece temperature of 20°C.
[0153] Step S40, prepare gray mica iron oxide flakes as micro-flaky materials, wherein the mica iron oxide flakes have an average surface area of 900 square microns and an average thickness of 3 microns, each scale is formed by stacking multiple nanoscale flakes, and the average surface area of the nanoscale flakes is 260,000 square nanometers and the average thickness is 40 nanometers.
[0154] Step S50, spraying with micro-scale material. Specifically, plasma spraying technology is used to spray micro-scale material on the transition layer to form a non-stick layer with a thickness of 20 microns. The spraying parameters of plasma spraying are: current is 600A; voltage is 80V; main gas (argon) flow rate is 2000L / h; hydrogen flow rate is 70L / h; powder feeding gas flow rate is 40L / h; powder feeding amount is 30g / min; spraying distance is 20cm; spraying angle is 40°; workpiece temperature is 20°C, thereby completing the manufacture of the cookware of Example 1.
[0155] Example 2
[0156] The cookware of Example 2 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the surface area of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 360,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0157] Example 3
[0158] The cookware of Example 3 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the surface area of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 4900 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0159] Example 4
[0160] The cookware of Example 4 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the average thickness of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 10 nanometers) to replace the micro-flaky materials of Example 1.
[0161] Example 5
[0162] The cookware of Example 5 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the average thickness of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 50 nanometers) to replace the micro-flaky materials of Example 1.
[0163] Example 6
[0164] The cookware of Example 6 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the surface area of the primary structure is different. The specific parameters include: the average surface area of the scales is 3600 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0165] Example 7
[0166] The cookware of Example 7 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the surface area of the primary structure is different. The specific parameters include: the average surface area of the scales is 50 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0167] Example 8
[0168] The cookware of Example 8 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the average thickness of the primary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 1 micron, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0169] Example 9
[0170] The cookware of Example 9 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the average thickness of the primary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 5 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0171] Example 10
[0172] The cookware of Example 10 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the primary structure is different. The specific parameters include: the average surface area of the scales is 50 square microns, the average thickness is 1 micron, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0173] Embodiment 11
[0174] The cookware of Example 11 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the primary structure is different. The specific parameters include: the average surface area of the scales is 3600 square microns, the average thickness is 5 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0175] Example 12
[0176] The cookware of Example 12 is manufactured by the same method as that of Example 1, except that in step S10, a different material (the material of the cookware base in this embodiment is titanium alloy) is used to manufacture the cookware base of Example 1.
[0177] Embodiment 13
[0178] The cookware of Example 13 is manufactured by the same method as that of Example 1, except that in step S10, a different material (the material of the cookware base in this embodiment is stainless steel) is used to manufacture the cookware base of Example 1.
[0179] Embodiment 14
[0180] The cookware of Example 14 was manufactured on a cookware substrate using the same method as in Example 1, except that the thickness of the non-stick layer was 150 μm.
[0181] Embodiment 15
[0182] The cookware of Example 15 was manufactured on a cookware substrate using the same method as in Example 1, except that the thickness of the non-stick layer was 100 μm.
[0183] Example 16
[0184] The cookware of Example 16 is manufactured on the cookware substrate by the same method as Example 1, except that after step S50, the non-stick layer is further oxidized and hydrated to bring glyceryl stearate into contact with the treated non-stick layer to form a fatty acid modified layer with a thickness of 0.08 microns on the non-stick layer.
[0185] Embodiment 17
[0186] The cookware of Example 17 is manufactured on the cookware substrate by the same method as Example 1, except that after step S50, the non-stick layer is further oxidized and hydrated to bring glyceryl stearate into contact with the treated non-stick layer to form a fatty acid modified layer with a thickness of 0.12 μm on the non-stick layer.
[0187] Embodiment 18
[0188] The cookware of Example 18 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used to replace the micro-flaky materials of Example 1 and form non-stick layers separately. The micro-flaky materials of this embodiment include a plurality of first micron-sized flakes and a plurality of second micron-sized flakes, wherein the first micron-sized flakes have an average surface area of 50 square microns to 900 square microns and an average thickness of 1 micron to 2 microns, and the second micron-sized flakes have an average surface area of 900 square microns to 3600 square microns and an average thickness of 3 microns to 5 microns. The first micron-sized flakes are used to form a first sublayer with a thickness of 10 microns on the substrate, and then the second micron-sized flakes are used to form a second sublayer with a thickness of 10 microns on the first sublayer, thereby obtaining a non-stick layer in which the interlayer structures of the sublayers are arranged alternately in the thickness direction of the non-stick layer.
[0189] Embodiment 19
[0190] The cookware of Example 19 is manufactured by the same method as Example 18, except that in step S40, different micro-flaky materials are used to replace the micro-flaky materials of Example 1 and the non-stick layers are formed separately. The second micron-sized scales are used to form a first sublayer with a thickness of 10 microns on the substrate, and then the first micron-sized scales are used to form a second sublayer with a thickness of 10 microns on the first sublayer, thereby obtaining a non-stick layer in which the layer gap structures of each sublayer are arranged alternately in the thickness direction of the non-stick layer.
[0191] Comparative Example 1
[0192] The cookware of Comparative Example 1 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is phlogopite, wherein the phlogopite is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0193] Comparative Example 2
[0194] The cookware of Comparative Example 2 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium iron mica, wherein the lithium iron mica is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0195] Comparative Example 3
[0196] The cookware of Comparative Example 3 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is hydroxyferric mica, wherein the hydroxyferric mica is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0197] Comparative Example 4
[0198] The cookware of Comparative Example 4 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is biotite, wherein the biotite is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0199] Comparative Example 5
[0200] The cookware of Comparative Example 5 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium mica, wherein the lithium mica is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0201] Comparative Example 6
[0202] The cookware of Comparative Example 6 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is kaolinite, wherein the kaolinite is flaky, the average surface area of the scales is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0203] Comparative Example 7
[0204] The cookware of comparative example 7 is manufactured by the same method as in example 1, except that in step S40, a different material (the material in this example is phlogopite, wherein the phlogopite is flaky, has no secondary structure, has a flaky area of 900 square microns, and has an average thickness of 3 microns) is used to replace the micro-flaky material of example 1.
[0205] Comparative Example 8
[0206] The cookware of Comparative Example 8 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium iron mica, wherein the lithium iron mica is flaky, has no secondary structure, and the average surface area of the scales is 900 square microns and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0207] Comparative Example 9
[0208] The cookware of Comparative Example 9 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is hydroxyferric mica, wherein the hydroxyferric mica is flaky, has no secondary structure, and the average surface area of the scales is 900 square microns and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0209] Comparative Example 10
[0210] The cookware of comparative example 10 is manufactured by the same method as in example 1, except that in step S40, a different material (the material in this example is biotite, wherein the biotite is flaky, has no secondary structure, the average surface area of the scales is 900 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of example 1.
[0211] Comparative Example 11
[0212] The cookware of Comparative Example 11 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium mica, wherein the lithium mica is flaky, has no secondary structure, the average surface area of the scales is 900 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0213] Comparative Example 12
[0214] The cookware of Comparative Example 12 was manufactured in the same manner as in Example 6, except that after step S40, the substrate was heated to 80° C., peanut oil was applied to the non-stick layer and kept for 5 minutes, the surface of the non-stick layer was subsequently wiped with a rag, and the substrate was placed in a sintering chamber at 280° C. for 1 minute.
[0215] The cookware in Examples 1 to 19 and Comparative Examples 1 to 12 were tested, and the test results are shown in Table 1 below.
[0216] 1. Test methods and evaluation criteria
[0217] 1. Initial non-stick test method and evaluation criteria
[0218] Initial non-stickiness test method: GB / T32095.2-2015 fried egg non-stickiness test method. This method is an initial non-stickiness test, which is divided into levels Ⅰ, Ⅱ, and Ⅲ. Level Ⅰ has the best non-stickiness and level Ⅲ has the worst non-stickiness.
[0219] 2. Test method and evaluation criteria for long-lasting non-stick properties
[0220] Long-lasting non-stick test method: Long-lasting non-stick test method in GB / T32388-2015, the unit is the number of times, the higher the number, the longer the life, the non-stick result is evaluated once every 500 times, and the number of times when it is used to level III is recorded.
[0221] 3. Hardness test method and evaluation standard
[0222] The Vickers hardness test method is used to test the Vickers hardness of the obtained cookware coating, where the hardness value unit is HV. The larger the measured hardness value, the harder the sample is, the stronger the non-stick layer is resistant to abrasion by shovels and food materials, and the less likely it is to be worn. Therefore, the service life of the non-stick layer is longer. Generally speaking, the hardness of the non-stick layer is expected to be no less than 200HV.
[0223] 4. Corrosion resistance test methods and evaluation standards
[0224] Prepare a 5% sodium chloride solution, add 1 / 3 of the volume of the pot, cover and keep it boiling. Observe the rust on the pot surface every half an hour until obvious rust appears and stop the experiment.
[0225] For the corrosion resistance test, it is expected that the corrosion resistance of the sample can reach more than 2h.
[0226] 2. Test Results
[0227] Table 1 Test results
[0228]
[0229] As can be seen from Table 1, the non-stick layer formed by stacking inorganic non-metallic materials in the present application has good non-stickiness, long-lasting non-stickiness, hardness and corrosion resistance. Too large or too small scales will affect non-stickiness and long-lasting non-stickiness. At the same time, the thickness of the non-stick layer has a direct impact on the hardness and corrosion resistance. The thicker the non-stick layer, the higher the hardness and the better the corrosion resistance.
[0230] According to the present application, the inventors have found that when the size of the flakes exceeds the selected range, the non-stickiness and long-lasting non-stickiness of the non-stick layer are significantly reduced, even below the standard requirements. Specifically, when the flakes of the micro-flaky material are too large, it will affect the micro-melting effect of the flakes during the preparation of the non-stick layer, resulting in the non-stick layer being stacked less densely and producing too large a gap, which in turn affects the flotation effect of water and air in the gap, resulting in a decrease in non-stickiness; when the flakes of the micro-flaky material are too small, the flakes will over-melt during the preparation of the non-stick layer, resulting in the non-stick layer being stacked too densely and without an appropriate gap, which will also affect the entry of water and air into the gap, and the flotation effect cannot be effectively produced, resulting in a deterioration in non-stickiness.
[0231] Although the present invention has been specifically shown and described with reference to exemplary embodiments of the present invention, it will be understood by those skilled in the art that various changes in form and detail may be made herein without departing from the spirit and scope of the present invention as defined by the claims and their equivalents. The embodiments should be considered in a descriptive sense only and not for the purpose of limitation. Therefore, the scope of the present invention is not limited by the specific embodiments of the present invention, but by the claims, and all differences within the scope will be interpreted as included in the present invention.
Claims
1. A non-stick layer, characterized in that: At least the surface layer of the non-stick layer has a layer gap structure, which is formed by stacking a plurality of micro-scale flake materials, which are formed by stacking a plurality of nano-scale flakes, and the layer gap structure has a plurality of micron-scale gaps, and there are a plurality of nano-scale gaps between adjacent micron-scale gaps.
2. The non-stick layer according to claim 1, characterized in that The size of the micron-scale gap is 1 micron-10 microns, and the size of the nanoscale gap is 50 nanometers-200 nanometers; and / or, The nanometer-scale gap and the micrometer-scale gap are irregular shapes.
3. The non-stick layer according to claim 1, characterized in that The micro-scale flake material is a micron-sized flake, and the surface area of the micron-sized flake is 50 square microns to 3600 square microns, and the thickness is 1 micron to 5 microns.
4. The non-stick layer according to claim 1, characterized in that The surface area of the nanoscale flakes is 4900 square nanometers to 360,000 square nanometers, and the thickness is 10 nanometers to 50 nanometers; and / or, In micro-scale materials, the gaps between adjacent nanoscale scales are in the range of 50 nanometers to 200 nanometers.
5. The non-stick layer according to claim 1, characterized in that The micro-scale material is an inorganic non-metallic material.
6. The non-stick layer according to claim 5, characterized in that The inorganic non-metallic material includes micaceous iron oxide or a modified product of micaceous iron oxide.
7. The non-stick layer according to claim 6, characterized in that The non-stick layer includes a plurality of sub-layers stacked in layers, and the interlayer structures of the sub-layers are arranged alternately in the thickness direction of the non-stick layer.
8. The non-stick layer according to claim 1, characterized in that The thickness of the non-stick layer is 10 micrometers to 150 micrometers; and / or, The hardness of the non-stick layer is 600 HV to 1100 HV; and / or, The non-stick layer has a temperature tolerance of 800°C-1200°C.
9. The non-stick layer according to claim 1, characterized in that The non-stick layer is connected with a fatty acid salt modified layer, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the non-stick layer.
10. The non-stick layer according to claim 9, characterized in that The oil comprises at least one of stearin, palmitin and olein.
11. A method for manufacturing a non-stick layer, characterized in that: The method comprises the following steps: Providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes; The surface of the micro-scale flaky material is micro-melted, so that the micro-scale flaky material is stacked to form a non-stick layer having a layer structure with a plurality of micron-scale gaps, wherein a plurality of nano-scale gaps are provided between adjacent micron-scale gaps.
12. The method for manufacturing a non-stick layer according to claim 11, characterized in that: The step of slightly melting the surface of the micro-scale material comprises: heating the micro-scale material with plasma, supersonic flame, electric arc or laser as an energy source to slightly melt the surface of the micro-scale material.
13. A non-stick cooker, characterized in that: The non-stick cookware comprises a substrate and a non-stick layer formed on the substrate, wherein the non-stick layer comprises the non-stick layer according to any one of claims 1 to 10 or comprises a non-stick layer manufactured by the method for manufacturing a non-stick layer according to claim 11 or 12.
14. The non-stick cookware according to claim 13, characterized in that: The non-stick cookware also includes: A transition layer is formed of a metal material and is formed between the substrate and the non-stick layer.
15. The non-stick cookware according to claim 14, characterized in that The metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy; and / or, The thickness of the transition layer is 8 micrometers to 80 micrometers.